SOCIALIZATION OF ASSISTANCE IN THE DEVELOPMENT OF THE INDEPENDENT CURRICULUM AT THE MGMP IPS MTs CITY OF PADANG - Susanti, Nora; Wati, Wati; Erita, Erita; Rahmania, Meri; Saputra, Syailendra Eka (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2025)
This community service activity aims to improve the understanding and competence of Social Sciences (IPS) subject teachers in implementing the Independent Curriculum at the Madrasah Tsanawiyah (MTs) level throughout Padang City. Through a participatory approach, this activity was carried out in the form of training, group discussions, and intensive mentoring for teachers who are members of the Social Studies Subject Teachers' Council. The results of the activity showed that the Social Studies teachers experienced an increase in their understanding of the basic principles of the Independent Curriculum, including the concept of learning differentiation, designing teaching modules based on local contexts, and integrating the values of the Pancasila Student Profile in Social Studies learning. In addition, this activity strengthens the role of the teacher council as a forum for collaboration between educators to share good practices and develop strategies for implementing a more effective curriculum. This service is expected to be the first step in building a more reflective, adaptive, and in-line social studies learning ecosystem in line with the direction of national education policy.Keywords: Independent Curriculum, MGMP, Pancasila Student Profile